Two-stage heat recovery system equipped with thermoelectric elements. (25th February 2021) - Rednic, V.; Gutt, R.; Bruj, E.; Bot, A.
Highlights: Complex system with two recovery stages for wasted heat extraction. Efficiency computation model of the recovered energy. Comparison of ANSYS Fluent simulations and experimental measurements for three designs of the heat recovery system. Adaptive energy balance of different types of output power for specific requirements. Abstract: Purpose: A huge amount of the world's electric energy is produced by fossil fuels, which release wasted heat in the form of exhaust flue gases. This wasted thermal energy can be recovered into utilizable thermal and/or electric energy. In this paper we present a two-stage heat recovery system equipped with thermoelectric elements, used to extract the thermal energy exhausted by the burning chamber of a Stirling engine. Materials and methods: The optimization process of the design was performed using ANSYS Fluent software. The initial design has been manufactured to correlate the numerical parameters with the physical ones. Based on the good results acquired, three designs with different ratios of energy output types are presented. Moreover, a theoretical model for the estimation of the extracted energy is proposed. Results and discussions: Within an error rate of 6 %, the numerical results are in good agreement with the experimental ones and the heat recovery estimations, showing that 44 % of the wasted flue energy is recovered as useful thermal and electric energy. Conclusions: We successfully designed a versatile two-stage heat recovery system, which first extracts thermal energy by keeping the pressure drop as low as possible without hindering the combustion process and which provides thereby the optimum temperature range for the thermoelectric elements mounted in the second part. The system was realized and tested in real operating conditions.